IMPLEMENTATION OF TEACHING AND LEARNING APPROACHES FOR INFANTS AND YOUNG CHILDREN IN NURSERIES: MEETING THE ASPIRATIONS - NURUL AIN DZUL KHARI; MOHD NAZRI ABDUL RAHMAN (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
This study was conducted to examine the implementation of the teaching and learning approach (PdP) for infants and toddlers in Nursery and to assess the extent to which the approach meets the aspirations of today's parents. This study uses interviews with Nursery teachers and library research as the main source. Through interviews, the researcher obtained a real picture of daily PdP practices such as the play-while-learning approach, routine-based learning and child-centered activities. Library research also helps strengthen the findings by reviewing early education theories and policies such as the PERMATA National Curriculum and the views of local and international scholars. The results of the study show that the teachers at the nursery implement PdP which emphasizes the comprehensive development of children from emotional, cognitive, social and physical aspects. However, challenges such as time constraints, high number of teachers with children and lack of technological facilities were also identified. This study concludes that the implementation of PdP in Nursery is already on a good track but needs to be improved in terms of professional teacher training, the provision of interesting teaching aids as well as continuous cooperation between parents and Nursery management so that early childhood education continues to be relevant and of good quality.